Distressed Acquisitions: Evidence from European Emerging Markets - Ichiro Iwasaki; Evžen Kocenda; Yoshisada Shida (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We analyze factors behind 23,213 distressed acquisitions in European emerging markets from 2007–2019. Besides the impact of financial ratios, legal form, ownership structure, firm size, and age, we emphasize the role of institutions and channels of their propagation. We show that the quality and enforcement of insolvency laws are linked with the lower probability of distressed acquisitions, followed by corruption control and progress in banking reforms. The impact of institutions is larger in less-advanced countries as compared to economically stronger ones. The effect of institutions increased after the financial crisis but declined as the economic situation improved.
Keywords: C35; D02; D22; E02; G34; K20; L22; 330; distressed acquisitions; mergers; European emerging markets